14% recoverable strain in Ni52.87Mn23.82Ga23.32 microwires. (1st February 2017) - Ding, Zhiyi; Zhu, Jie; Zhang, Xinzhen; Liu, Dexing; Qi, Qingli; Zhang, Yong; Cong, Daoyong
Abstract: Shape memory alloys exhibit superelasticity and shape memory properties by virtue of a reversible phase transformation between austenite and martensite. Here, 14% recoverable strain is reported in a Heusler-type Ni52.87 Mn23.82 Ga23.32 microwire, fabricated by rapid solidification via the Taylor method, with a diameter of 110 µ m. The microwire exhibits superelastic strain of 11%, very low Young's modulus of 5.5 GPa, critical stress of 110 MPa and mechanical stability during cyclic tensile test. We attribute this enhanced ductility and large superelasticity to the stress-induced martensitic phase transformation. The energy conversion and the structure of martensitic phase induced by stress are also discussed.